1994
DOI: 10.1111/j.1439-0426.1994.tb00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and pathogenicity of a Bacillus sp. associated with a septicaemic condition in some tropical freshwater fish species

Abstract: Observations made over a three-year period at the Fish Diseases Laboratory of the African Regional Aquaculture Centre (ARAC), Nigeria, revealed the gradual emergence of a new, highly infectious septicaemic condition in some widely cultivated freshwater fish species. The broad host range included: Heterobanchus bidorsalis, Clarias gariepinus, "Heteroclarias" (a hybrid of these two species, male and female respectively), Chrysichthys nigrodigitatus, and Cyprinus carpio. Clinical signs and pathological lesions as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…Most bacteria species were identified, present in Clarias gariepinus (Table 2), which include both pathogenic and normal flora. These bacteria species found in the tissues of C. gariepinus in this study were similar to the ones isolated in cultured C. gariepinus by Emikpe et al (2011) and Oladosu et al (2011). The occurrence of these bacteria species in different organs of fish (Figures1 to 3), could be an indication of presence of certain predisposing as handling of the fish, feeding of the fish, changing water as at when necessary and also cleaning and disinfecting the ponds.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Most bacteria species were identified, present in Clarias gariepinus (Table 2), which include both pathogenic and normal flora. These bacteria species found in the tissues of C. gariepinus in this study were similar to the ones isolated in cultured C. gariepinus by Emikpe et al (2011) and Oladosu et al (2011). The occurrence of these bacteria species in different organs of fish (Figures1 to 3), could be an indication of presence of certain predisposing as handling of the fish, feeding of the fish, changing water as at when necessary and also cleaning and disinfecting the ponds.…”
Section: Resultssupporting
confidence: 89%
“…The gills had the highest bacteria count (0.0109±0.0030 x 10 5 cfu/g) while the skin had the least bacteria count (0.0066±0.0102 x 10 5 ) for fish tissues from Woji. These contamination was less in contrast with the work done on wild and cultured C. gariepinus in Ibadan by (Emikpe et al, 2011) and also with the work done on C. gariepinus in Abeokuta by (Oladosu et al, 2011). This is higher than the set standard for the acceptable level of microbiological safety of foods which is 1-100cfu/g (Ayinla et al, 1994).…”
Section: Resultsmentioning
confidence: 73%
“…Sequencing of the 16S rRNA gene revealed that the Gram-positive bacteria from common carp and rainbow trout belonged to different groups and were distinguished from the other members of the genus. The outcome was that the common carp (B2 carp) and rainbow trout isolates (B1 Rt) matched entries in the database for B. mycoides (homology = 100%) and B. pseudomycoides (homology = 99%), respectively (Table 3; Figure 3) indistinguishable phenotypically and could not be differentiated by means of the tests used in this study (Logan & DeVos, 2009;Nakamura, 1998 (Oladosu, Ayinla, & Ajiboye, 1994), bacillary necrosis (Ferguson et al, 2001) and gill disease. Thus, B. cereus and B. subtilis were associated with branchionecrosis in common carp (Pychynski, Malanowska, & Kozlowski, 1981) and striped bass (Baya, Lupiani, & Hetrick, 1992).…”
Section: Pathogenicity Determinationmentioning
confidence: 84%
“…The sharply increasing water temperatures were most likely an important trigger for the onset of disease. Certainly, there have been some previous reports of Bacillus as fish pathogens, causing generalized necrotizing dermatitis (Oladosu, Ayinla, & Ajiboye, ), bacillary necrosis (Ferguson et al., ) and gill disease. Thus, B. cereus and B. subtilis were associated with branchionecrosis in common carp (Pychynski, Malanowska, & Kozlowski, ) and striped bass (Baya, Lupiani, & Hetrick, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the reported works on infections in fishes include Angka, et al (1995), they observed virulence characteristics of Aeromonas hydrophila in which A. hydrophila killed Clarias gariepinus after five days. In Nigeria, Oladosu et al (2007) also demonstrated the pathogenicity of Bacillus sp. to fishes.…”
Section: Introductionmentioning
confidence: 97%